2021
DOI: 10.1002/slct.202100294
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Electrochemical Characterization of NaCoO2 as Cathode Material in 2 M NaOH Aqueous Electrolyte

Abstract: This work reports an electro‐analytical study of NaCoO2 as cathode material synthesized by a low‐temperature combustion method for aqueous sodium‐ion batteries. The synthesized cathode material was electrochemically characterized in 2 M NaOH aqueous electrolyte. The obtained material‘s physical characteristics are investigated by X‐Ray Diffraction (XRD), Scanning Electron Microscopy (SEM), Energy Dispersive X‐ray analysis (EDX), Thermo‐Gravimetric Analysis (TGA) and Differential Scanning Calorimetry (DSC) to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The XRD pattern of NaTi 2 (PO 4 ) 3 anode material has been reported in our work previously. 13 The surface morphology and structure of the material was determined using scanning electron microscope (SEM). Figures 3A-3D show typical SEM image of NFPC at different magnifications, i.e., 2 μm, 1 μm, 500 nm and 200 nm respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The XRD pattern of NaTi 2 (PO 4 ) 3 anode material has been reported in our work previously. 13 The surface morphology and structure of the material was determined using scanning electron microscope (SEM). Figures 3A-3D show typical SEM image of NFPC at different magnifications, i.e., 2 μm, 1 μm, 500 nm and 200 nm respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Initially, in ARSBs, layered transition metal oxides (LTMO) were introduced and studied their Na + insertion/de-insertion properties. [8][9][10][11] Recent studies in ARSBs showed successive result with P2-Na 0.57 CoO 2 , 12 NaCoO 2 , 13 Na 4 MnV(PO 4 ) 3 -rGO, 14 Na 4 Mn 9 O 18 / reduced grapheme oxide (NMO-RGO). 15 Despite of having these success stories of sodium-based aqueous rechargeable batteries, there is an increased concern on improving the energy storage capacity of the ARSBs.…”
mentioning
confidence: 99%
“…), conversion-based materials (oxygen-, phosphor-, sulfur-, and selenium-based materials, for example, MS x with M = Sn, Sb, Mo, Fe, Co, Ni, Mn), and alloying-based materials (e.g., Si, Ge, Sn, Sb, and Bi). 22−25 There are also different types of SIB cathode materials according to structure classification: twodimensional layer transition metal oxide, Na 1−x MO 2 (M = Fe, 26 Ti, 27 Co, 28 V, 29 Ni, 30 etc. ), 31 two-or three-dimensional layer transition metal oxide and fluorides (such as NaFeF 3 , 32 NaNiF 3 , 33 etc.…”
Section: Introductionmentioning
confidence: 99%
“…According to the reaction mechanism, the anode can be divided into three types: insertion-based materials (including titanium-based oxide and carbonaceous materials, such as TiO 2 , graphene, soft carbon (SC), hard carbon (HC), etc. ), conversion-based materials (oxygen-, phosphor-, sulfur-, and selenium-based materials, for example, MS x with M = Sn, Sb, Mo, Fe, Co, Ni, Mn), and alloying-based materials (e.g., Si, Ge, Sn, Sb, and Bi). There are also different types of SIB cathode materials according to structure classification: two-dimensional layer transition metal oxide, Na 1– x MO 2 (M = Fe, Ti, Co, V, Ni, etc. ), two-or three-dimensional layer transition metal oxide and fluorides (such as NaFeF 3 , NaNiF 3 , etc.…”
Section: Introductionmentioning
confidence: 99%